Petroleum Hydrocarbons PHC in Sediments of Three Different Ecosystems from Southeast Coast of India - Muthukumar, A (International Journal of Pharmaceutical & Biological Archive, 2013)
Petroleum Hydrocarbons PHC in Sediments of Three Different Ecosystems from Southeast Coast of India